2014
DOI: 10.4054/demres.2014.31.45
|View full text |Cite
|
Sign up to set email alerts
|

The gender divide in urban China: Singlehood and assortative mating by age and education

Abstract: OBJECTIVEChinese media labels highly educated, urban women who are still single in their late 20s as "leftover ladies." We investigate whether indeed highly educated women are less likely to marry than their less-educated counterparts, and how assortative mating patterns by age and education play a role in singleness. METHODSWe use data from the urban samples of the Chinese General Social Surveys in the 2000s. In the analysis we calculate marriage rates to examine the likelihood of entry into marriage, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 54 publications
3
92
0
Order By: Relevance
“…In the feudal and imperial eras, when marriage was largely a familial arrangement rather than the result of an individual choice, marriage was intended to represent a balanced "mutual exchange of ritual obligations and material wealth" between two families, which is inferred and recognized by the wider public through visible signs such as occupational status and the presentation of a dowry (Mann 2011: 57). In many respects, the tradition of marriage of matching doors resembled the prevailing assortative mating in Western societies, which has been extensively discussed in previous research (e.g., Becker 1973;Fernandez and Rogerson 2001;Kalmijn 1991;Qian and Qian 2014): It sanctioned marriage between two parties of equal social standing, which in turn served to reinforce preexisting social hierarchies. However, the practice of marriage of matching doors also had unique characteristics derived from Chinese traditions.…”
Section: The Tradition Of Marriage Of Matching Doorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the feudal and imperial eras, when marriage was largely a familial arrangement rather than the result of an individual choice, marriage was intended to represent a balanced "mutual exchange of ritual obligations and material wealth" between two families, which is inferred and recognized by the wider public through visible signs such as occupational status and the presentation of a dowry (Mann 2011: 57). In many respects, the tradition of marriage of matching doors resembled the prevailing assortative mating in Western societies, which has been extensively discussed in previous research (e.g., Becker 1973;Fernandez and Rogerson 2001;Kalmijn 1991;Qian and Qian 2014): It sanctioned marriage between two parties of equal social standing, which in turn served to reinforce preexisting social hierarchies. However, the practice of marriage of matching doors also had unique characteristics derived from Chinese traditions.…”
Section: The Tradition Of Marriage Of Matching Doorsmentioning
confidence: 99%
“…Third, because Chow and Chen (1994) found that Chinese women actively seek upward social mobility in the marriage market in contemporary China, the female occupational hypergamy specification limits the associations to the cells in the contingency tables in which (a) the husband had a higher occupational status than his wife's father, (b) the wife had a lower occupational status than her husband's father, and (c) the wife's father had a lower occupational status than the husband's father at the time of marriage. Finally, as Table 2 shows, the odds of marriage across distinct occupational status categories may depend on how many levels of difference an individual crosses (Qian and Qian 2014). As it may be less difficult for individuals to marry a partner in an adjacent occupational status category than across two or more categories, the occupational crossings specification assumes that the odds of an individual crossing each (additional) occupational barrier in the contingency table differ (see Qian and Qian [2014] for further information on the crossings model).…”
Section: Fatherfather-in-law Associationmentioning
confidence: 99%
See 1 more Smart Citation
“…The LPM model was adapted to explore the effect of comparative supply on marriage decision: on the marriage choice of low educated; sexratio i,p described the comparative supply individual i's group facing, equals female share while considering female's marriage choice, male share for male; Y i describes individual i's personal characteristics, including age; Z p is the province fixed effect and ε i,p is the random component. choice of urban high educated women by census year and age group, while Table 7 shows the results considering the effect of male share on rural low educated men 8 .…”
Section: Empirical Analysismentioning
confidence: 99%
“…Columns 1, 3 and 5 in Table 6 are the basic regression on gender interacted 8 Regression results considering urban low educated male and rural high educated female are available on request. But as their age increases, more men tend to marry with younger women, with the percentage stayed comparatively steady after age 30.…”
Section: Empirical Analysismentioning
confidence: 99%